The Effect of Qualitative Exercises (Physical - Skill) in the Development of Rapid Strength and Lay up Scoring of Basketball Players - Mazen Kadhim Nassif (Journal of Global Pharma Technology, 2016)
Through the follow-up of the researchers of most educational and training units, they noticed that most players aged 13-15 suffer from weakness in the strength and speed of the strike of the arms and legs, which negatively affects the performance and difficulty of scoring points during the performance of lay-up scoring, since the way to achieve the ideal performance that aims to win requires the compatibility of many requirements, including a high level of performance interrelated and overlapping physical and skill capabilities among them, as physical capacity is the cornerstone on which to build the development of the skill, so researchers have considered this problem Through the preparation of exercises qualitative (physical - skill) and trying to overlap them to serve the skill performance attempt to develop the rapid force and lay-up scoring of basketball players. The objective of the research was to identify the effect of specific exercises (physical - skill) in the development of rapid strength and lay-up scoring of players in basketball. The imposition of research is a positive effect of the physical exercises (physical - skill) in the development of fast power and lay-up scoring of basketball players. The researchers used the experimental method in designing the one group to suit the nature of the problem to be solved, and represented the research in all members of the research community; the young players aged 13-15 years in the club sports fans - Kerbala, the 10 players. The most important conclusions were of specific exercises (physical - skill) and clearly affected the development of rapid power and the skill of lay-up pacification of basketball players. The recommendations are the need to pay attention to the specific exercises and the link between the physical and skill aspects during the exercise and the single training unit. And the need to pay attention to the training of the force of the fast because it described the physical task is needed basketball player effectively and continuouslyKeywords: qualitative exercises, Rapid strength and lay up scoring.